Emergence and characterization of a novel ST627-KL8 carbapenem-resistant Klebsiella pneumoniae lineage associated with ICU transmission in a tertiary hospital, China - Pang, Xiaoxiao; Xu, Guoxin; Zheng, Yu; Ding, Chao; Zhang, Wei; Du, Hong; Chen, Long (Frontiers in Microbiology, 2026)
IntroductionCarbapenem-resistant Klebsiella pneumoniae (CRKP) poses a serious threat to public health. We characterized a rarely reported ST627-KL8 CRKP lineage associated with intensive care unit (ICU) transmission.MethodsThree isolates (ZJG29565, ZJG30140, and ZJG30146) were obtained from three patients in the ICU and subjected to antimicrobial susceptibility testing. Whole-genome sequencing (WGS) was performed to determine genomic characteristics, phylogenetic relationships, and plasmid content, followed by assessments of mucoviscosity, capsule quantification, serum resistance, and bacterial virulence using a Galleria mellonella (G. mellonella) infection model. Additionally, bacterial capsule morphology was observed via transmission electron microscopy (TEM).ResultsSNP analysis (≤ 5 SNPs) confirmed clonal transmission within the ICU. Phylogenetic analysis placed ST627-KL8 as a distinct lineage closely related to ST14. All isolates carried an IncFIIK34 plasmid encoding blaKPC–2, consistent with their carbapenem-resistant phenotype. Phenotypic assays—including TEM, mucoviscosity testing, serum resistance, and uronic acid quantification—demonstrated a thinner capsule and reduced mucoviscosity compared with the KL2 reference strain. In the Galleria mellonella model, ST627-KL8 exhibited intermediate virulence (66.7%–76.7% survival), between the hypervirulent K. pneumoniae ATCC 43816 strain (30.0%) and the low-virulence K. pneumoniae ATCC 700603 strain (96.7%).DiscussionThis study identified a novel ST627-KL8 CRKP clone with intermediate virulence, consistent with its reduced capsule phenotype and lack of classical hypervirulence genes. These features, together with the subtle clinical presentations, may contribute to reduced clinical vigilance and delayed optimization of antimicrobial therapy. Importantly, ST627-KL8 CRKP carried the IncFIIK34blaKPC–2 plasmid, which has been reported to exhibit high conjugation frequency, posing a significant challenge in clinical settings.